(untitled) (Tzintzun, Revista de Estudios Históricos, 2023)
The history of the Headquarters of Military Operations in Mexico has been practically unexplored. This article offers an approach to the creation and operation of this territorial military organization between 1917 and 1923, which includes the governments of Venustiano Carranza and Álvaro Obregón, before the development of the Delahuertista rebellion. The military division reflected the difficulties of pacifying the country and political recentralization. These processes did not end with the rise of the Sonora group to power in 1920; on the contrary, their arrival led to the development of new rebel movements, some local and others planned by exiles from the United States. The uprisings forced the federal Executive to reorganize, like a chessboard, the men who commanded the headquarters, who almost always became political operators of the center, but also occasional accomplices of the uprisings and even leaders of them.